Action Research: From Concept to Model of Forming Autopoietic Building Blocks as Life Circle - Tanja Balažic Peček; Franc Brcar; Boris Bukovec (Izzivi Prihodnosti, 2018)
Research question (RQ): How -with the concept of forming autopoietic building blocks - to develop a model of organization of future which will be able of self-/co-organization and self-/co-production in life circle? We are studying human potential as a natural circular process, which is characteristic of action research. Autopoiesis is a complete intertwinement of fields of continuous movement, which is consequently shown in creativity andholistic culture of a person. Purpose: To developed a concept of forming autopoietic building blocks as life circle and a model of organization as a model of organization of future. We are interested in a human in organization, in interpersonal co-dependence and self-/co- dependence on micro and macro level. Inside this more and more virtual organization we are studying a human, humanity and human potential as a creative potential of humane organization. Method: Direction in action research, which is supported with mixed methods for comprehensive study of autopoiesis in organization. For qualitative research we used Atlas.ti software. This research can be classified as case study. Results: For designing autopoietic building blocks as life circle we developed a concept in 5 steps. With results of qualitative and quantitative analysis, comparison of autopoietic, modern and 4.0 organization, we developed a »Model of forming autopoietic building blocks in organization –MOGAO«. The model can be a comparative tool for perceiving processes in an organization. With results we claim that 4.0 organization is oriented mostly towards action and is getting stronger in improved communication. However, it decreases in emotions and thinking of a human. Organization: Results can serve as a guideline and challenge to humane organizations. We present the challenge how – by knowing horizontal and vertical laws of a human – we can »control« 4.0 organization. The research contributes to awareness of a human and to transformation of allopoietic to more and more autopoietic organizations in direction of: »Autopoietic 4.0 Human (r)evolution«. Society: Accepting autopoiesis on all levels of society and consequently emerging organizations, as well as society as a whole. The final result is to influence by autopoiesis the cultural development of society in the sense of connecting science, art, high technologies and spirituality. Originality: Interlacement of horizontal and vertical scientific areas by connecting natural and social sciences. Recording of autopoietic principles (building blocks of processes) from point of view of an observer and a creator as »self-/co-«principles. Completeness of studying with the developed concept and model »MOGAO« .